2002
DOI: 10.1124/jpet.300.2.428
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I-Converting Enzyme Inhibition Increases Cardiac Catecholamine Content and Reduces Monoamine Oxidase Activity via an Angiotensin Type 1 Receptor-Mediated Mechanism

Abstract: Antihypertensive and cardioprotective effects of angiotensin I-converting enzyme (ACE) inhibitors are well established and have usually been attributed to the inhibition of angiotensin II (ANG)-mediated effects at vascular or ventricular (angiotensin type 1) AT 1 receptors. One other important mechanism involves ANG-induced interactions with the sympathetic nervous system, which might include alterations of cardiac catecholamine concentrations during ACE inhibition due to a modulation of monoamine oxidase (MAO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 25 publications
2
13
0
1
Order By: Relevance
“…In another study, we have also demonstrated that ex-vivo pretreatment with the same MAO inhibitors attenuated the endothelial dysfunction in aortic rings harvested from spontaneously hypertensive rats (Sturza et al 2013b). It has been previously reported in the literature that treatment with angiotensin II converting enzyme inhibitors reduced MAO activity, suggesting that activation of the renin-angiotensin-aldosterone system may be responsible for the enzymatic induction (Raasch et al 2002). Furthermore, in-vitro or in-vivo application of selegiline, the irreversible MAO-B inhibitor, elicited vasodilatation via an increase in the amount of nitric oxide in brain tissue and cerebral blood vessels (Shiva 2010).…”
Section: Discussionmentioning
confidence: 95%
“…In another study, we have also demonstrated that ex-vivo pretreatment with the same MAO inhibitors attenuated the endothelial dysfunction in aortic rings harvested from spontaneously hypertensive rats (Sturza et al 2013b). It has been previously reported in the literature that treatment with angiotensin II converting enzyme inhibitors reduced MAO activity, suggesting that activation of the renin-angiotensin-aldosterone system may be responsible for the enzymatic induction (Raasch et al 2002). Furthermore, in-vitro or in-vivo application of selegiline, the irreversible MAO-B inhibitor, elicited vasodilatation via an increase in the amount of nitric oxide in brain tissue and cerebral blood vessels (Shiva 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Some studies indicated that cardiac MAO-A regulates noradrenaline concentrations. 15,16 Our demonstration that MAO-A is also an important source of H 2 O 2 in the heart suggests that this enzyme may contribute to ROS-dependent cardiomyocyte apoptosis. To verify this hypothesis, we investigated the potential role of ROS generated by MAO-A during 5-HT degradation in cardiomyocyte death and the role of MAO in post-I/R cardiac damage.…”
Section: Clinical Perspective P 3305mentioning
confidence: 99%
“…16 More recently, it was reported that inhibition of the renin-angiotensin system decreases cardiac MAO activity. 17 Whether there is an interaction between Ang II and MAO in vessels is not known. Ang II is well known to activate and induce other sources of ROS like vascular NADPH oxidases, 18 and Ang II also increases vascular xanthine oxidase activity.…”
Section: Sturza Et Al Maos In Endothelial Dysfunction 141mentioning
confidence: 99%